2022
DOI: 10.1021/acs.energyfuels.2c02122
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Thermal Behavior and Molecular Architecture of Asphaltenes by a Thermal-Optical Carbon Analyzer Coupled to High-Resolution Mass Spectrometry

Abstract: In the past decade, extensive molecular-level research on asphaltenes, primarily based on mass spectrometric approaches, acknowledged the coexistence of two primary architecture motifs, “island” single-core- and “archipelago” (multi-core)-type structures. Nonetheless, analytical methods for a classification are still limited. In this study, the thermal desorption and pyrolysis behavior of a diverse set of asphaltenes covering island- and archipelago-enriched samples and their extrographic fractions has been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Coke formation during thermal analysis has also been linked to the predominant structural motif. Island-type asphaltenes revealed potentially higher amounts of residue due to their high content in highly aromatic compounds, which serve already as coke precursors. ,,, …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Coke formation during thermal analysis has also been linked to the predominant structural motif. Island-type asphaltenes revealed potentially higher amounts of residue due to their high content in highly aromatic compounds, which serve already as coke precursors. ,,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…Island-type asphaltenes revealed potentially higher amounts of residue due to their high content in highly aromatic compounds, which serve already as coke precursors. 35,37,40,41 Figure 9 shows the mass loss curves from thermogravimetric measurements (black line) as well as the temperature-resolved total summed intensity detected by APPI-FT-ICR MS (red line). The yellow and the gray lines represent the temperatureresolved summed intensity for all compounds of the S x -class and HC-class.…”
Section: Dominant Structural Motifs Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Analytical pyrolysis is a common tool used to give insights into chemical structures of samples that are hardly accessible by conventional gas and liquid chromatography because of a low vapor pressure or poor solubility, e.g., chars from biomass and plastic pyrolysis 78,79 or asphaltenes in crude oil. 80,81 Organic species that have not evaporated up until the end of OC2 are characterized by a low vapor pressure, and they rather degrade thermally than evaporate in OC3 and OC4 (480 and 580 °C). This analytical pyrolysis induces a shift in mass evolving organic compounds from higher m/z ranges to low ones below m/z 100, and evolving species can be analyzed with a SPI-TOF-MS. 76 For BCB emissions, it was found that the evolving patterns of low molecular species resulting from analytical pyrolysis in OC3 and OC4 changed substantially with varying CO emissions.…”
Section: Low-volatile Organics From Solid-fuel Combustion: a Transiti...mentioning
confidence: 99%